Intrusive history and volatile evolution of the Endeavour porphyry Cu-Au deposits, Goonumbla district, NSW, Australia - Lickfold, V (2002)
The Goonumbla Volcanic Complex (GVC) of central-west New South Wales, Australia, is part of the Ordovician Macquarie Island Arc. The upper unit of the GVC, the Wombin Volcanics, comprises submarine shoshonitic lavas and associated volcaniclastic rocks, and hosts four economic porphyry Cu-Au deposits, Endeavour 22 (E22), E26, E27 and E48. Together these deposits have a combined ore reserve of 63.6Mt @ 1.1 % Cu and 0.5g/t Au. Mineralisation is centred on thin, pipe-like quartz monzonite porphyry (QMP) complexes that intruded the Wombin Volcanics in an extensional regime towards the end of the Late Ordovician. Despite being some of the smallest economic porphyry deposits in the world in terms of tonnage and cross-sectional area, detailed pit mapping and drillcore logging has led to the recognition of eight intrusive phases within the QMP complexes of the Endeavour deposits. The oldest intrusive phase is a coarse-grained, equigranular monzodiorite intrusion that is restricted to the deeper parts of E26. This intrusion has a sheared contact with the next oldest phase, equigranular to weakly porphyritic biotite quartz monzonite (BQM) intrusions, which are recognised at all four deposits. A series of three variably felsic QMP phases emplaced over a short period of time after the BQM comprise the central QMP complexes; 1) volumetrically minor early- and late-mineral biotite phyric QMP (B-QMP) dykes and dykelets, 2) volumetrically dominant syn-mineral K-feldspar phyric QMP intrusions (K-QMP) and 3) less abundant syn-to late-mineral augite-biotite K-feldspar phyric QMP (KA-QMP) intrusions, which intruded the cores of the K-QMP bodies. Basaltic trachyandesite dykes and augite phyric monzorute porphyry (\zero\" porphyry) dykes at E26 represent post-mineral phases of intrusive activity associated with the Endeavour deposits. Mafic dykes of uncertain age also intrude the Endeavour deposits. Four main stages of hydrothermal activity have been recognised at each deposit. The Early Stage associated with the intrusion of the BQM ...